The managerial flash sales dash: Is there advantage or disadvantage at the finish line?. (April 2016) - Berezina, Katerina; Semrad, Kelly J.; Stepchenkova, Svetlana; Cobanoglu, Cihan
Abstract: The central intent of this qualitative inquiry is to investigate the benefits, drawbacks, and performance measures of hotel room inventory distribution via flash sales websites. Key advantages and disadvantages of using such a distribution channel fall within the categories of inventory management, revenue management, brand marketing, customer relationships, and operational challenges. The significance of the study is in providing a comprehensive review of the flash sales phenomenon in the lodging industry that may assist hotel managers with the performance evaluation of this distribution channel. Using grounded theory methodology, a flash sales evaluation framework was developed based on 46 phone interviews with hotel managers from different segments of the American hotel industry.